Pesantren Based Character Education: An Analysis of Tebuireng’s Five Foundational Principles in Contemporary Islamic Education - Isnan Badarudin Kamal; Asriana Kibtiyah (Journal Of Islamic Education And Pesantren, 2024)
Contemporary Islamic education faces persistent challenges in the form of character crises, declining integrity, and rising intolerance within increasingly plural societies. These conditions call for character education models that move beyond normative discourse and enable sustainable value internalization within educational practice. This study aims to analyze the Five Core Principles of Tebuireng—sincerity (ikhlas), honesty, responsibility, diligence, and tolerance—as a framework for character education rooted in the pesantren tradition within the context of contemporary Islamic education. Employing a qualitative approach with a library research with field-based reflection design, the study grounds its analysis in relevant theoretical literature while reflecting on empirical findings drawn from a thesis-based field study of character education practices at Tebuireng Islamic Boarding School. The findings reveal that the Five Core Principles function as a living and operational value system, internalized through institutional structures, educator–student relationships, and the pesantren’s collective culture. Character education is not transmitted through verbal instruction alone but is embodied through habituation, role modeling, and direct moral experience. These findings affirm the role of the pesantren as a moral community that supports holistic and sustainable character formation. The study contributes to the theoretical strengthening of Islamic character education based on habituation and exemplarity, while offering practical insights for advancing character education and religious moderation in contemporary Islamic educational contexts.